PEMBUATAN NANOPAR TIKEL LixMn2O4 - Wigayati, Etty Marti (LIPI Press, 2009)
LixMn2O4 nanoparticle has been prepared using Li2CO3 and MnO2 as starting materials. Firstly, Li2CO3 and MnO2 were mixed using solid state reaction, then the powder was calcinated at 700oC and sintered at 800oC. The resulted pouder was characterized using SEM, XRD, and EIS (Electrochemical Impedance Spectroscopy). Henceforth, LixMn2O4 powder was processed into nanoparticle size through milling process using PBM (Planetary Ball Milling) for 80 hour and ultrasonificator with power of 300 watt for 2 hour. The characterization was conducted again using SEM, XRD, PSA and EIS. The result shows that there is no diffraction pattern change after the milling process. Examination using SEM shows particle changes from needles to round shapes with smaller sizes. Diffraction analyzes using Rietveld method results in lattice parameter of 8.23454 , cell unit volume of 558.3647 3 and the crystal structure is cubic with space group of Fd-3m. The particle size of the final product is analyzed using Particle Size Analyzer (PSA) which results in the value of 178 nm in average diameter. The measurement of electrical impedance gives values of 2 M ohm (before milling) and 8 M ohm (after milling).